Communication, class and concentric media practices: Developing a contemporary rubric1. (May 2014) - Wolfson, Todd; Funke, Peter N
Understanding class as a process of self-making in relation to a particular, historical form of capitalism, in this article we argue that media and communication (from face-to-face and old mediums such as radio to internet-powered tools) must be conceptualized as an emerging structural dimension for class formation. Based on ethnographic fieldwork on the Media Mobilizing Project in Philadelphia, a community-based media and communications infrastructure and a network of organizations across the region, we develop a conceptual approach we call concentric practices, which provides us with a framework of how contemporary class formation is occurring through the use of media and communications. Concentric practices we understand and analyze along three overlapping processes, which establish a "common" among the different fragments of the working class: communicative spaces, narrative practices and shared struggles. Analytically, these concentric practices describe a process of thickening and converging of the atomized and fractured neoliberal working class. This model can be employed as a heuristic framework for a host of similarly situated dynamics, aiding in teasing out and better understanding processes of class formation under neoliberal capitalism.